Agricultural Innovation and Sustainable Development - Blakeney, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book deals with sustainable agriculture at a time of climate change. It seeks to identify a number of solutions to deal with the agricultural stresses caused by climate change. These range from the identification and cultivation of appropriate crop varieties and the adoption of climate adaptive agricultural practices. Significant sustainable agricultural innovation is required to deal with these challenges. Intellectual property rights (IPRs) may be of crucial importance for modern agriculture. They serve to make R&D in agriculture attractive, by encouraging investment in new technologies and generating tradeable assets. A number of the chapters of this book refer to the principal IPRs relevant to agricultural innovation, namely: (i) patents, which protect inventions; (ii) plant variety rights, which protect the breeding of new and distinct plant varieties; and (iii) trademarks and geographical indications, which facilitate the marketing of products by providing protection for the symbols of their manufacturing or geographic origin. The United Nations Climate Change Panel has urged the consideration of the agricultural practices of traditional communities and some of these practices particularly involving rice, banana, and brassica cultivation are explored in the book. This book is essential reading for officials of governments and international organizations concerned with sustainability, as well as scholars and students concerned with these subjects